2018
DOI: 10.1159/000489296
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia-Related Acute Pancreatitis

Abstract: Acute pancreatitis (AP) is an inflammatory disease presenting from mild localized inflammation to severe infected necrotic pancreatic tissue. In the literature, there are a few cases of hypothermia-induced AP. However, the association between hypothermia and AP is still a myth. Generally, mortality from acute pancreatitis is nearly 3–6%. Here, we present a 40-year-old chronic alcoholic female who presented with acute pancreatitis induced by transient hypothermia. A 40-year-old chronic alcoholic female was hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Mildly elevated serum amylase without clinical evidence of pancreatitis is common in the state of hypothermia, being present in 50 to 65% of patients [1,[17][18][19], and as the body temperature decreases, the serum amylase levels rise [18]. Due to the absence of epigastric abdominal pain in this patient, acute pancreatic inflammation has not been ini-tially diagnosed.…”
Section: Discussionmentioning
confidence: 80%
“…Mildly elevated serum amylase without clinical evidence of pancreatitis is common in the state of hypothermia, being present in 50 to 65% of patients [1,[17][18][19], and as the body temperature decreases, the serum amylase levels rise [18]. Due to the absence of epigastric abdominal pain in this patient, acute pancreatic inflammation has not been ini-tially diagnosed.…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown that internal rewarming strategies do not provide any extra benefits, and complications related to coagulation and bleeding can result [12]. Uncomplicated mild to moderate acute pancreatitis in hypothermic patients is conservatively managed with efforts to normalize temperature, aggressive fluid resuscitation, and antibiotic therapy [13]. However, moderately severe or severe acute pancreatitis is managed in the ICU with consideration given to surgical therapy based on the complications.…”
Section: Discussionmentioning
confidence: 99%
“…Peneliti mendapatkan hasil bahwa riwayat konsumsi alkohol tidak punya hubungan yang signifikan dengan stabilitas thermoregulasi, hal ini sejalan dengan penelitian yang dilakukan Patrizio bahwa pada pasien hipotermia, terjadi peningkatan keparahan penyakit tidak terkait dengan suhu awal, jenis kelamin, alkohol atau trauma (Petrone P et al 2020). Namun penelitian tersebut tidak sejalan dengan Kyawzaw Lin, yaitu ada beberapa kasus yang diindikasi hipotermia namun sementara akibat penyalah gunaan alkohol kronis (Lin, K et al, 2018). Minuman beralkohol bereaksi pada tubuh manusia dengan melebarkan pembuluh darah sehingga panas tubuh dapat didistribusikan dengan cepat, hal ini dapat memberikan sensasi hangat pada tubuh manusia.…”
Section: Tingkat Efektifitas Blanket Warmer Terhadap Stabilitas Therm...unclassified